Introduction: Ritual in Biblical Text and Biblical Lands - Garroway, Kristine Henriksen (Advances in ancient Biblical and Near Eastern research, 2021)
The papers in this special issue speak to the numerous ways in which thinking about the Hebrew Bible within its ancient Near Eastern cultural and intellectual environment can provide new insights and further the understanding of ritual in the biblical world. Papers herein look outwards to Israel’s neighbors both near and far in their examination of ritual and cult in this life and the next. The authors cull from a variety of approaches, from philological (comparative literatures), iconographic (visual exegesis), and archaeological (material culture) to explore biblical texts as cultural products and "textual artifacts" of ancient Israel.